Proficiency of allocentric and egocentric wayfinding: a comparison of schoolchildren with young adults and older adults. (11th May 2022) - Rinne, Klara; Memmert, Daniel; Bock, Otmar
Abstract: Wayfinding skills decay in old age, more so for wayfinding in an allocentric than an egocentric reference frame. This study investigates whether wayfinding deficits of schoolchildren mimic those of older adults. Schoolchildren were tested on two wayfinding tasks: one could only be mastered in an allocentric, and the other only in an egocentric reference frame. The results were compared with those from a previous study of young and older adults who had been tested on the same two wayfinding tasks. It was found that wayfinding performance improved somewhat from school age to young adulthood and that this improvement proceeded more or less in parallel for the allocentric and the egocentric tasks. It was further found that wayfinding performance decayed from young to older adulthood and that this decay was more dramatic for the allocentric than for the egocentric task. This pattern of findings does not support the hypothesis that the wayfinding performance of schoolchildren mimics that of older adults.